Evidence-Based Advocacy for Municipal Climate Change Action. (March 2020) - Mitchell, Carrie L.; Graham, Alexandra
In this article, we argue that evidence-based advocacy for climate change action should be a core competency of professional planners. However, data from our case study in Metro Vancouver, Canada, suggests that municipal-level climate change practitioners have conflicting views regarding their professional responsibility to advocate for action on climate change. We contend these tensions stem from twentieth-century planning debates, which oscillate between rational-comprehensive planning versus calls to advocate, in one form or another, for various public interests. Overall, we find that transforming barriers into enablers of action on climate change must include critical engagement with planning theory and education.